The effects of speed endurance training on aerobic and anaerobic performance of young female soccer players - Cherdsak Kaewkamda; Piyawat Luesopha; Widsarut Sekaew; Wareerat Kokittipong; Pruchaya Chumvangvapee; Sarawuth Thassanawiwath; Ban Chabairam; Noppadon Imsud; Kornruch Markjaroen; Pornpimon Rungruangsin (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: This study examines the impact of speed endurance training on the aerobic and anaerobic capacities of young female soccer players. The research focuses on assessing the physiological adaptations resulting from structured high-intensity training, which is crucial for enhancing soccer performance.